Evaluation of Amine Functionalized Thermal Power Plant Solid Waste for Industrial Wastewater Remediation - Ali Y. Kozbek; Kubilay Şahin; Ertuğrul Sarı; Esra Bedir; Fatma G. Yüce; Senem Çitoğlu; Hatice Duran (Adsorption Science & Technology)
Micro/nanoparticles generated after the combustion of coal/lignite in the thermal power plants were modified with amino groups of (3-aminopropyl) triethoxysilane (APTES). These silane-based functional particles were applied in textile dye (xylenol orange, XO and methyl orange, MO) removal process to deal with an industrial wastewater problem. The maximum adsorption efficiencies of APTES coated micro/nanoparticles for MO and XO dye molecules were calculated to be around 98% and 75%, respectively. The adsorption behavior of the LCFA against dyes is also assessed by investigating the effect of adsorbent dosage, contact time, pH, and temperature. The optimum dye removal was observed at a pH of 4.0, and the equilibrium was achieved within 5 min. The maximum uptake capacities of LCFA-APTES for MO and XO dye molecules were calculated to be around 17.91 and 14.72 mg g−1, respectively. This value is approximately 3 − 5 times higher than the similar adsorbent in the literature. The uptake mechanism of MO and XO dyes onto LCFA-APTES is governed by electrostatic interaction and hydrogen bonding between dye molecules and APTES. The surface chemical modifications and the nature of functional groups were ascertained by scanning electron microscopy (SEM), thermogravimetric analysis (TGA), X-ray fluorescence (XRF), and X-ray photoelectron spectroscopy (XPS). The application of recovered micro/nanoparticles from solid wastes and their utilization for wastewater treatment is important not only for economy of developing countries but also for protecting the environment.